2011
DOI: 10.1016/j.jtcvs.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Use of a nonpledgeted suture technique is safe and efficient for aortic valve replacement

Abstract: Objective The use of pledgeted sutures to secure the prosthetic valve to the annulus during aortic valve replacement is thought to decrease the incidence of paravalvular leak. We hypothesized that use of nonpledgeted sutures in aortic valve replacement would provide equivalent outcomes to those of a pledgeted suture technique. Methods Between January 1995 and April 2009, a total of 802 patients (511 nonpledgeted, 291 pledgeted) underwent isolated aortic valve replacement, including 671 patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
3
14
0
3
Order By: Relevance
“…Pledgeted horizontal mattress sutures with large braided suture materials have long been used as a standard suture technique for MVR [ 1 ]. One study has demonstrated that the use of a nonpledgeted horizontal mattress suture technique during aortic valve replacement did not increase the rate of PVL in comparison with the use of a pledgeted suture technique [ 7 ]. In the present study, a major PVL occurred in 1.1% of patients in the P group and 2.9% of patients in the N group, which was a non-significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pledgeted horizontal mattress sutures with large braided suture materials have long been used as a standard suture technique for MVR [ 1 ]. One study has demonstrated that the use of a nonpledgeted horizontal mattress suture technique during aortic valve replacement did not increase the rate of PVL in comparison with the use of a pledgeted suture technique [ 7 ]. In the present study, a major PVL occurred in 1.1% of patients in the P group and 2.9% of patients in the N group, which was a non-significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we review 10 years of our experience with nonpledgeted sutures during MVR to assess whether this technique is equivalent to a pledgeted technique with respect to operative mortality, the rate of major PVL, and the rate of prosthetic valve endocarditis. A recent study has shown that the nonpledgeted horizontal mattress suture technique during aortic valve replacement is safe and time efficient [ 7 ], but no study concerning the use of a nonpledgeted horizontal mattress suture technique during MVR has previously been published.…”
Section: Introductionmentioning
confidence: 99%
“…We prefer to place nonpledgeted horizontal mattress sutures from the ventricle to the aorta. 26 The sutures are passed through the prosthetic valve and the valve is seated in the annulus. Care must be ensured that the coronary ostia are not obstructed by the valve posts or sewing ring.…”
Section: Our Approach To Minimally Invasive Aortic Valve Replacement mentioning
confidence: 99%
“…LaPar a spol. 8 srovnávají dvě skupiny pacientů po prosté náhradě aortální chlopně implantované jednotlivými stehy s podložkami a bez podložek. Stejně jako v našem souboru jediným statisticky významným rozdílem je délka studené ischemie a délka mimotělního oběhu.…”
Section: Diskuseunclassified